Securing small and medium ports and their supply chain services - Kyranoudi, Pinelopi; Polemi, Nineta (Frontiers in Computer Science, 2023)
This paper argues that Small and Medium sized Ports (SMPs) are as important as larger ones in terms of Supply Chain Service (SCS) management and security, as they can become the weakest links for national and European Union (EU) resilience and security. It focuses on explaining key concepts about SMPs, their characteristics (e.g., size, operational field, infrastructure), potential threats (e.g., interception of sensitive information, illegal access, terrorism) and attacks (cyber, cyber-physical), as well as basic security concepts (e.g., attack path, attack vector, risk). Three SCS attack scenarios for SMPs are described based on different types of threats, which could cause catastrophic impacts, even paralyzing an SMP propagated in its SCS. Finally, a Risk Management methodology for SCSs that can be used by SMPs, named CYSMET, is presented considering their capabilities, needs and constraints.